2001
DOI: 10.1051/animres:2001140
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties, gross composition, energy value and nitrogen fractions of Haflinger nursing mare milk throughout 6 lactation months

Abstract: -The trends of the physicochemical properties, chemical constituents and main nitrogen fractions of Haflinger mare milk were studied. Milk samples were collected at d 4,20,40, 60, 80, 120, 150 and 180 post-partum, by hand-milking from 5 mares, 7-14 years old (4-11 parities) and 400-490 kg live weight. Density, pH, titratable acidity, fat, protein, lactose and ash varied significantly during the first lactation period, while the freezing point showed statistically no significant modifications. The contents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
37
3
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 19 publications
21
37
3
4
Order By: Relevance
“…In a study by Doreau et al (1986), lactose and energy intake by the suckling foal increased daily, whereas fat intake decreased and protein intake remained constant during the first 8 wk of lactation. In the current study, the lactose curve (Figure 1) showed a different shape with a continuous increase during the lactation period, which agrees with other authors (Mariani et al, 2001).…”
Section: Model Fitsupporting
confidence: 92%
“…In a study by Doreau et al (1986), lactose and energy intake by the suckling foal increased daily, whereas fat intake decreased and protein intake remained constant during the first 8 wk of lactation. In the current study, the lactose curve (Figure 1) showed a different shape with a continuous increase during the lactation period, which agrees with other authors (Mariani et al, 2001).…”
Section: Model Fitsupporting
confidence: 92%
“…The decreases in total N and casein N contents of Haflinger mare's milk from day 4 to day 180 are in agreement with the observations reported by other studies (Minieri and Intrieri 1970;Mariani et al 1993Mariani et al , 2001). The same trends were observed in other breeds and/or for shorter lactation periods (Neseni et al 1958;Bowman and van der Schee 1978;Gibbs et al 1982;Oftedal and Jenness 1988;Doreau et al 1990;Smolders et al 1990;Mariani et al 1993;Csapó-Kiss et al 1995).…”
Section: Discussion Nitrogen Composition Of Mare's Milksupporting
confidence: 92%
“…2c). Similarly, data on mare's milk did not show marked variations in lipid content from d 40 to 150 of lactation [30].…”
Section: Milk Compositionmentioning
confidence: 76%
“…Recent clinical studies confirm ass's milk feeding as a safe and valid treatment of most complicated cases of multiple food intolerance [7]. However, information on ass's milk composition [11,26,37,43] is more limited than that on mare's milk [18,19,29,30,33,38], which has also been studied as an infant food [5,15].…”
Section: Introductionmentioning
confidence: 99%